The Evaluation of Industrial Based Learning Program to Improve Vocational Student Skills Competency - Marlina, Marlina (INVOTEC, 2016)
This study was conducted based on the refinement or improvement of vocational secondary education to anticipate the future needs and challenges to be continuous alignment with the needs’ development of the business world of work, the development of science, technology, art and culture. The result of field observation syndicate that the majority of graduates of vocational schools (SMK) cannot be absorbed in the job, since the competent cites they have do not fulfill the demands of the working world yet. Problem formulation of this researches "What industrial-based learning that can improve the competence of women's fashion of vocational student sat dressmaking program? The research applies the evaluation research with the approach of model program evaluation CIPP (context, input, process, and product). The population is all classes of X1 vocational schools in the City and County of Bandung, while the sample is the three vocational schools that apply the 2013 curriculum which covers a fashion industry. Results of the study are: 1.The contexts of industrial-based learning programs that exist at the time being are in accordance with the competency skills women's clothing needed by the industry. 2. The existing industry-based learning programs is appropriate. It is based on the data: a. The students’ condition: background, motivations, and plans after graduation, b. The teachers’ condition: the educational background and learning experience, and .c. Industrial needs. The entire programs which have been developed 90% are in accordance with the needs of industry, d. Facility: there are still about 10-20%, which are not fulfilled yet. 3. The process consists of three parts, namely: planning, implementation and evaluation. The effectiveness of the learning plan already match the views of the suitability of the formulation KI2, KI3, KI4, with the basic competencies, indicators and goals. The Implementation learning category is very appropriate, since it was applying the method, the media, the type of assessment and learning environment in accordance with the purpose of learning that is able to apply factual knowledge, conceptual and procedural. The evaluation of learning activities in schools are already using authentic assessment. 4. The product. Based on the previous evaluation context, input and process, there are component of the industrial-based learning program that has been running quite effective, but there are also some that have not been effective, yet. The conclusions of research are: Industrial-based learning program evaluation through the model CIPP (context, input, process, and product) is accomplished quit optimal, thus recommends that the program should not be stopped, but it requires modification of the model on the program before continuing.